PENGARUH LIKUIDITAS, SOLVABILITAS, EFISIENSI DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Afiva Nuzurrahma; Irham Fahmi (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
Abstract: This study aims to determine whether the ratios of liquidity, solvency, efficiency and profitability on financial difficulties in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2019.The sample used in this study as many as 13 companies obtained through purposive sampling method.This study tested the panel data regression using Eviews 10 software. The results of this study indicate that the liquidity ratio has a significant positive effect on financial difficulties. The solvency ratio has a negative and significant effect on financial distress. The efficiency ratio has no effect and is not significant on financial distress. Profitability ratio has a positive and insignificant effect on financial distress. The results of simultaneous testing of liquidity ratios, solvency, efficiency and profitability have an effect on financial difficulties.